Challenging poverty with green space in informal settlements of Quito (Research, Society and Development, 2021)
Planners increasingly recognize the value of green spaces to the wellbeing of urban residents. Research on ecosystem services has produced much of what is known about such value, although the attention is mainly on the cities’ core while informal settlements remain overlooked. Using a case study of informal settlements in Quito, this paper focuses on how their residents use the neighboring green space to fight poverty. The study uses data from interviews, field notes, and archives to show how green spaces escalate the capabilities of the neighboring residents to access everyday resources. A preserved landscape enhances the ability to walk and travel to everyday destinations; allotments reduce the reliance on debts with shop keepers to access food; and sports fields enable income generation and pursue a career.  These findings provide an understanding of how to address simultaneously environmental, social, and economic challenges in cities of developing countries. Planners engaged in the sustainable development agenda would benefit from this research.